Self-experience and the feeling of being oneself - Schmidt-Boddy, Philipp (Universitätsbibliothek Heidelberg, 2021)
This is the unaltered manuscript of the Phd thesis as submitted at Heidelberg University. This dissertation aims to clarify the role of self-experience for the notion of selfhood. To this aim, it examines the epistemology, metaphysics, and phenomenology of self-experience, notably, in its most basic forms. Against three forms of skepticism about self-experience widespread in the history of philosophy, it argues that self-experience is informative with regard to the being of selfhood and that self-experience is best understood as the very way of being of selfhood. On this view, self-experience, in its most basic form, constitutes what is essential about selfhood. Moreover, it is suggested that self-experience, even in its most basic form, involves a sense of existence which is best described as a feeling of being oneself.
Keywords: Hochschulschrift